Clinical and Aetiological Profile of Thrombocytopenia in Adults: A Cross-sectional Study - MD Hussain D Page; Preeti Gupta; Trupti Pisal (National Journal of Laboratory Medicine)
Introduction: Thrombocytopenia, characterised by low platelet count, is a common haematological condition associated with various infectious diseases, including dengue and malaria. Understanding the relationship between the severity of thrombocytopenia and bleeding manifestations is crucial for effective patient management. Aim: To determine the clinical and aetiological profile of patients with thrombocytopenia and assess the association between the severity of thrombocytopenia and bleeding manifestations across different conditions. Materials and Methods: This cross-sectional study was carried out at a tertiary care hospital from July 2022 to January 2024 and a total of 197 patients with platelet counts below 150,000/μL were included. Patients were categorised based on their platelet counts and World Health Organisation (WHO, 1981) bleeding grades. Clinical data, including demographics, laboratory findings and bleeding manifestations, were collected and analysed. The need for platelet transfusion was assessed in relation to the severity of thrombocytopenia. Descriptive statistics were used and results presented in means and percentage. Results: Dengue (n=97, 49.2%), malaria (n=47, 23.9%) and sepsis (n=19, 9.6%) were the most frequent aetiological causes of thrombocytopenia, with P. vivax malaria diagnosed in 31 (65.9%) of the malaria patients. Physical examination revealed skin manifestations (petechiae, purpura, bruises, ecchymosis and hyperpigmentation) in 14 (60.9%) patients, followed by bleeding gums in 8 (34.8%) patients. The prevalence of moderate thrombocytopenia (75,000-150,000/μL) was noted in 73 (37.1%) patients, while only 40 (20.3%) had severe thrombocytopenia with platelet counts <25,000/μL. Among the 23 patients with bleeding, 16 (69.6%) had WHO grade 1, with 15 (65.2%) requiring platelet transfusion. Conclusion: The study highlighted the high prevalence of moderate thrombocytopenia in patients with dengue and malaria. Patients with moderate and severe thrombocytopenia presented with bleeding manifestations and required platelet transfusion.